Innovation Of Business Models Based On Sharing Economy In Rural Entrepreneurship Ecosystems - Alfa Syahputra; Burhan Bungin; Thomas S. Kaihatu (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
The rapid growth of the sharing economy has reshaped entrepreneurial practices worldwide, yet its application in rural contexts remains underexplored. This study aims to investigate the opportunities, challenges, and innovative potentials of sharing economy-based business models within rural entrepreneurship ecosystems in Indonesia. Adopting a qualitative case study approach, data were collected from small and medium enterprises (SMEs), village entrepreneurs, and local communities through interviews, observations, and document analysis. Findings reveal that sharing economy practices can enhance resource efficiency, foster community collaboration, and promote sustainable rural development. However, significant challenges persist, including limited digital literacy, infrastructure constraints, and regulatory gaps. This research contributes to the literature by extending the discourse on sharing economy beyond urban contexts and provides practical insights for policymakers, SME actors, and technology developers seeking to strengthen rural entrepreneurship ecosystems.